ON THE COLLABORATION OF M.N. ZHIRKOV, FOUNDER OF THE YAKUT COMPOSER SCHOOL, AND YAKUT STORYTELLER U.G. NOKHSOROV: FROM THE HISTORY OF THE CREATION OF THE OPERA-OLONKHO (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the collaboration between M.N. Zhirkov and U.G. Nokhsorov in creating the first Yakut opera “Nurgun Bootur”. Their joint work resulted in a synthesis of traditional Yakut and professional Yakut musical art. The article describes the specifics of creating the genre of the Yakut opera-olonkho with the assistance of famous Yakut olonkhosuts, among whom a prominent place was occupied by the famous Amginsky epic storyteller, expert in traditional culture and ethnophor U.G. Nokhsorov. His contribution to the process of creating a musical drama, opera, and the first stage versions of this work is presented - he became one of its main interpreters in the stage version, performing almost all the leading parts. U.G. Nokhsorov fruitfully collaborated with M.N. Zhirkov not only during the creation of the opera, but also in the first years of its performance on the theater stage.
Keywords: M.N. Zhirkov, U.G. Nokhsorov, Yakut folk music, the first Yakut composer, folk singer, olonkhosut, ethnophor the first Yakut opera, olonkho opera, musical drama.